2009
DOI: 10.1007/s11099-009-0030-7
|View full text |Cite
|
Sign up to set email alerts
|

Pioneering research on C<sub>4</sub> leaf anatomical, physiological, and agronomic characteristics of tropical monocot and dicot plant species: Implications for crop water relations and productivity in comparison to C<sub>3</sub> cropping systems

Abstract: The review is done to summarise the history of the discoveries of the many anatomical, agronomical, and physiological aspects of C 4 photosynthesis (where the first chemical products of CO 2 fixation in illuminated leaves are four-carbon dicarboxylic acids) and to document correctly the scientists at the University of Arizona and the University of California, Davis, who made these early discoveries. The findings were milestones in plant science that occurred shortly after the biochemical pathway of C 3 photosy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 183 publications
0
10
0
2
Order By: Relevance
“…Some studies on these cultivars have suggested that cassava uses a C 3 –C 4 intermediate form of photosynthesis on account of high leaf photosynthetic rates, low apparent rates of photorespiration, a chlorenchymatous bundle sheath and a high photosynthetic nitrogen (N) use efficiency (El‐Sharkawy & Cock, ; El‐Sharkawy, , ). Parallel work feeding 14 CO 2 to leaves of cassava showed an apparent intermediate pattern of initial C 4 and C 3 products (Cock et al ., ).…”
Section: Increasing εC In Cassava Through Photosynthesismentioning
confidence: 99%
“…Some studies on these cultivars have suggested that cassava uses a C 3 –C 4 intermediate form of photosynthesis on account of high leaf photosynthetic rates, low apparent rates of photorespiration, a chlorenchymatous bundle sheath and a high photosynthetic nitrogen (N) use efficiency (El‐Sharkawy & Cock, ; El‐Sharkawy, , ). Parallel work feeding 14 CO 2 to leaves of cassava showed an apparent intermediate pattern of initial C 4 and C 3 products (Cock et al ., ).…”
Section: Increasing εC In Cassava Through Photosynthesismentioning
confidence: 99%
“…However, the relationship between cell size and photosynthesis remains unresolved, as illustrated by the contradictory hypotheses put forward by several authors. A negative correlation between photosynthesis and mesophyll cell size in several species was reported (El-Sharkawy and Hesketh, 1965;Wilson and Cooper, 1970;El-Sharkawy, 2009), attributed to the increase in cell surface area per volume with reduced cell size, but Dornhoff and Shibles (1976) observed no correlation between photosynthesis and cell size in soybean (Glycine max). In contrast, others (Warner et al, 1987;Edwards, 1988, 1989) argued that large cells have greater photosynthetic capacity than smaller cells.…”
mentioning
confidence: 99%
“…This approach is precise and more efficient (especially the fakir method in combination with confocal microscopy as shown by Albrechtová et al, 2007) than model-based methods. Its advantages have been acknowledged by other authors (El-Sharkawy, 2009). …”
Section: Surface Area Of Mesophyll Cells and Internal Leaf Surface Areamentioning
confidence: 80%